STRATEGIES FOR MARKETING AND SALES CHANNEL DEVELOPMENT: THE IMPACT OF INDIRECT CHANNELS ON BUSINESS EXPANSION (International Seven Journal of Multidisciplinary, 2023)
This article explores the influence of indirect sales programs on commercial expansion and market share growth. Through a case study approach, it investigates strategic marketing and the development of distribution channels, focusing on how indirect sales via intermediaries such as distributors, retailers, and partners allow companies to broaden their reach, optimize logistics, and foster loyalty among sales partners. The findings connect theory to practical experience with channel creation and incentive management, demonstrating how effective marketing and channel strategies drive sustainable growth and partner engagement.